Fluorescent labeling of human albumin using the new aromatic dialdehyde labels and the study of innerfilter effect - Muhammad Aminuddin; Sofia Ahmed; Muhammd Ali Sheraz; Iqbal Ahmad; Karamat Mahmood; J N Miller (Wolters Kluwer Medknow Publications, 2010)
The labels naphthalene-2,3-dicarboxaldehyde (NDA), 1-phenylnaphthalene-2,3-dialdehyde (fNDA), and anthracene-2,3-dialdehyde (ADA) have been used as fluorigenic reagents. They formed fluorescent derivatives with proteins. The derivatives formed are in fact isoindoles. The fluorescence decay of the labels-antibody was found to extend over a period of 4, 8, and 10 h for ΦNDA, ADA, and NDA-derivative, respectively. Protein formed is comparatively less stable as compared to simple amino acids. In relation to innerfilter effect, the addition of cytochrome C, myoglobin, and ATP as absorbers to label-human albumin fluorophores appeared to have quenched the fluorescence. In the case of using NDA as label, the fluorescence was quenched roughly 70%, 24%, and 58% for addition of cytochrome C, myoglobin, and ATP, respectively. The labels used were found to give rapid, reproducible, and reliable results.